DEVELOPMENT OF TECHNOLOGICAL PARAMETERS FOR WHEAT GRAIN GERMINATION - Safronova T.N.; Kazina V.V.; Safronova K.V. (Техника и технология пищевых производств)
Grain is available for any food product consumer. During germination, grain enzyme systems are activated, and splitting of complex nutrients to simpler ones which are easily digestible by the human body takes place. Dry wheat grain germination has been studied. Germination was carried out using a steam convection apparatus. Germination time dependence on temperature, conditioned air flow rate and humidity in the chamber of a steam convection apparatus has been defined. A mathematical model for the studied process has been developed, and the equation analysis has been fulfilled. Organoleptic, physical-chemical and microbial parameters of germinated grain have been determined. Germinated wheat grains were packed in vacuum bags and cooled rapidly to prevent contamination during storage. Quality control based on three test points and defining organoleptic and microbial parameters of germinated grains was carried out within 10 days of storage. The developed technology of wheat grain germination to the embryo root of 2 mm long using a steam convection apparatus has the following process conditions: humidity 100%, temperature 30 °C and air conditioning power of 0.09 kW. The period of vacuum packed grain storage has been defined as 7 days under the following storage requirements: temperature 4 ± 2 °С, humidity 75%.